An Unusual Case of Kidney Injury in a Young Woman with a Connective Tissue Disease - Roberto Rivera; Salvador Vila (Case Reports in Nephrology)
A 32-year-old female was admitted to our institution with thrombocytopenia, fever, serositis, hepatosplenomegaly, diffuse lymphadenopathy, and renal insufficiency. A diagnosis of systemic lupus erythematosus was made. Due to recalcitrant thrombocytopenia, serositis, and renal insufficiency methylprednisolone was prescribed in high doses. In addition to proteinuria and hematuria, she was found to have uric acid crystals in her urinalysis. A serum uric acid was found elevated at 18 mg/dL. Rasburicase infusions were started. Within 5 days of commencing rasburicase and continuing high-dose methylprednisolone, her serum creatinine normalized and proteinuria resolved. The microhematuria disappeared within 2 weeks of beginning rasburicase. The rapid reversal of renal insufficiency and all urinary abnormalities after the start of rasburicase infusions suggests that the renal injury was most likely due to uric acid-mediated renal injury and not lupus nephritis. Our case illustrates the co-occurrence of 2 distinct clinical entities, one common for the patient’s age, sex, and foremost clinical findings, while the other uncommon and unexpected, but both associated to kidney injury. Clinicians must be aware that careful evaluation of symptoms and laboratory tests is needed to make a thorough differential diagnosis and provide the right treatment at the most opportune moment.